PERILAKU LINGKUNGAN DAN POLA HIDUP SEHAT DI LINGKUNGAN KAMPUS (Studi Pada Mahasiswa Aktif BEM Universitas Riau Periode 2019/2020) - Herna "; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at BEM University of Riau. The purpose of this study was to determine the level and relationship between student knowledge variables about the ideal campus environment, student attitudes towards the campus environment and healthy lifestyle actions in the campus environment. The author uses quantitative research methods with simple random sampling, and inferential statistics as an analysis of sample data that results apply to the population. The total sample of 218 populations was 141 respondents. The data analysis technique used to test the relationship is the product moment correlation technique by using Student Knowledge Variables About the Ideal Campus Environment (X1), Student Attitudes Toward Campus Environment (X2) as predictors and the dependent variable is the Student's Healthy Lifestyle in Campus Environment (Y) . The results showed that the category of Student Knowledge about the Ideal Campus Environment was in the category of knowing with a percentage of 66.7%, Student Attitudes towards the Campus Environment were in the very good category with a percentage of 73.8%, and Healthy Lifestyle Actions in the Campus Environment were in the good category with a percentage of 56.7%. Correlation test results found there is a relationship between variables namely Student Knowledge About the Ideal Campus Environment (X1) and Student Attitudes Toward Campus Environment (X2) has a correlation with a value of 0.02 <0.05. Student Knowledge About the Ideal Campus Environment (X1) and Healthy Lifestyle Actions in the Campus Environment (Y) has a correlation with a value of 0.00 <0.05. Student Attitudes Toward Campus Environment (X2) and Healthy Lifestyle in Campus Environment (Y), has a correlation with the value of 0.00 <0.05. The positive significance of X1 - X2 significant value 0.253> 0.165, X1 - Y significant value 0.306> 0.165, and X2 - Y with a significant value 0.306> 0.165. Correlation coefficient values are in the third group with a value of 0.30 to 0.49 with a moderate interpretation of the relationship. It was concluded that, Environmental Behavior and Healthy Lifestyle in the Campus Environment On Active Students of BEM University of Riau in 2019/2020 had a positive and significant correlation in the correlation coefficient with moderate relationship interpretation. Keywords: Environmental Behavior, Healthy Lifestyle, Students